40 years of biannual family medicine research meetings – The European General Practice Research Network (EGPRN). (December 2013) - Buono, Nicola; Thulesius, Hans; Petrazzuoli, Ferdinando; Van Merode, Tiny; Koskela, Tuomas; Le Reste, Jean-Yves; Prick, Hanny; Soler, Jean Karl
Abstract Objective. To document family medicine research in the 25 EGPRN member countries in 2010. Design. Semi-structured survey with open-ended questions. Setting. Academic family medicine in 23 European countries, Israel, and Turkey. Subjects. 25 EGPRN national representatives. Main outcome measures. Demographics of the general population and family medicine. Assessments, opinions, and suggestions. Results. EGPRN has represented family medicine for almost half a billion people and > 300 000 general practitioners (GPs). Turkey had the largest number of family medicine departments and highest density of GPs, 2.1/1000 people, Belgium had 1.7, Austria 1.6, and France 1.5. Lowest GP density was reported from Israel 0.17, Greece 0.18, and Slovenia 0.4 GPs per 1000 people. Family medicine research networks were reported by 22 of 25 and undergraduate family medicine research education in 20 of the 25 member countries, and in 10 countries students were required to do research projects. Postgraduate family medicine research was reported by 18 of the member countries. Open-ended responses showed that EGPRN meetings promoted stimulating and interesting research questions such as comparative studies of chronic pain management, sleep disorders, elderly care, healthy lifestyle promotion, mental health, clinical competence, and appropriateness of specialist referrals. Many respondents reported a lack of interest in family medicine research related to poor incentives and low family medicine status in general and among medical students in particular. It was suggested that EGPRN exert political lobbying for family medicine research. Conclusion. Since 1974, EGPRN organizes biannual conferences that unite and promote primary care practice, clinical research and academic family medicine in 25 member countries.